2002
DOI: 10.1093/glycob/cwf052
|View full text |Cite
|
Sign up to set email alerts
|

Novel carbohydrate specificity of the 16-kDa galectin from Caenorhabditis elegans: binding to blood group precursor oligosaccharides (type 1, type 2, T , and T ) and gangliosides

Abstract: Galectins, a family of soluble beta-galactosyl-binding lectins, are believed to mediate cell-cell and cell-extracellular matrix interactions during development, inflammation, apoptosis, and tumor metastasis. However, neither the detailed mechanisms of their function(s) nor the identities of their natural ligands have been unequivocally elucidated. Of the several galectins present in the nematode Caenorhabditis elegans, the 16-kDa "proto" type and the 32-kDa "tandem-repeat" type are the best characterized so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
0
36
0
1
Order By: Relevance
“…In the C. elegans galectin Lec-6, the absence of these two residues confers broader carbohydrate specificity relative to that of the mammalian prototype galectins (28). The structural analysis of the CvGal CRDs by homology modeling strongly suggested that, although CvGal CRDs bind ␤-galactosyl residues, their specificity for N-acetylated disaccharides and oligosaccharides may differ from the mammalian galectins.…”
Section: Discussionmentioning
confidence: 99%
“…In the C. elegans galectin Lec-6, the absence of these two residues confers broader carbohydrate specificity relative to that of the mammalian prototype galectins (28). The structural analysis of the CvGal CRDs by homology modeling strongly suggested that, although CvGal CRDs bind ␤-galactosyl residues, their specificity for N-acetylated disaccharides and oligosaccharides may differ from the mammalian galectins.…”
Section: Discussionmentioning
confidence: 99%
“…Solid Phase Binding, Binding Inhibition, and Competitive Inhibition Assays-Solid phase lectin binding assays were carried out as described elsewhere (15,26). Briefly, 96-well microtiter plates were coated with neoglycoproteins, or untreated or glycosidase-treated authentic glycoproteins (10 g/ml in PBS), or hemocyte extracts (0.5 g/ml in PBS) for 3 h at 37°C.…”
Section: Characterization Of the Carbohydrate Specificity Of Rcvgal1mentioning
confidence: 99%
“…Recently, it has become apparent that the galectin family of lectins can also participate in the innate immune defense against pathogens (12). Galectins are present in all multicellular organisms, including worms, sponges, multicellular fungi, and insects (13)(14)(15)(16)(17)(18)(19). Galectins are PRRs in several types of organisms, and many mammalian pathogens express saccharide structures that are recognized by galectins.…”
mentioning
confidence: 99%